2009
DOI: 10.1038/sj.bjc.6604995
|View full text |Cite
|
Sign up to set email alerts
|

Activity of a novel, dual PI3-kinase/mTor inhibitor NVP-BEZ235 against primary human pancreatic cancers grown as orthotopic xenografts

Abstract: The phosphatidylinositol-3-kinase (PI3K)/Akt signalling pathway is frequently deregulated in pancreatic cancers, and is believed to be an important determinant of their biological aggression and drug resistance. NVP-BEZ235 is a novel, dual class I PI3K/mammalian target of rapamycin (mTor) inhibitor undergoing phase I human clinical trials. To simulate clinical testing, the effects of NVP-BEZ235 were studied in five early passage primary pancreatic cancer xenografts, grown orthotopically. These tumours showed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
66
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(74 citation statements)
references
References 26 publications
8
66
0
Order By: Relevance
“…S7A). Multiple studies have reported that high doses of NVP-BEZ235 resulted in weight loss in mouse models (31,32). After 4 weeks of treatment, NVP-BEZ235 reduced mouse body weight in a dose-dependent manner (Supplementary Fig.…”
Section: Dht Reduces Side Effects During Nvp-bez235 Treatmentmentioning
confidence: 99%
“…S7A). Multiple studies have reported that high doses of NVP-BEZ235 resulted in weight loss in mouse models (31,32). After 4 weeks of treatment, NVP-BEZ235 reduced mouse body weight in a dose-dependent manner (Supplementary Fig.…”
Section: Dht Reduces Side Effects During Nvp-bez235 Treatmentmentioning
confidence: 99%
“…Furthermore, BEZ235 displays a 2 log improvement in sensitivity over LY294002 (32) while not affecting other protein kinases. (32,33) BEZ235 exhibits strong antitumor activity in multiple in vitro and preclinical animal models (32,(34)(35)(36)(37) and is currently in phase I-II clinical trials for advanced solid tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the identification and characterization of PI3K pathway inhibitors with good drug-like properties were eagerly awaited to initiate clinical trials (8). NVP-BEZ235 is a dual PI3K/mTOR inhibitor that has proven its ability to significantly reduce the tumor growth of a number of human xenograft models (9)(10)(11), as well as of a murine PIK3CA driven lung tumor model (12). However, it is still unclear if compounds with a dual inhibitory profile would be equally efficacious in cancers with distinct genetic lesions in the PIK3CA, PTEN, HER2, or KRAS genes.…”
mentioning
confidence: 99%